Validation of a non-uniform meshing algorithm for the 3D-FDTD method by means of a two-wire crosstalk experimental set-up (2015)
This paper presents an algorithm used to automatically mesh a 3D computational domain in order to solve electromagnetic interaction scenarios by means of the Finite-Difference Time-Domain -FDTD-  Method. The proposed algorithm has been formulated in a general mathematical form, where convenient spacing functions can be defined for the problem space discretization, allowing the inclusion of small sized objects in the FDTD method and the calculation of detailed variations of the electromagnetic field at specified regions of the computation domain. The results obtained by using the FDTD method with the proposed algorithm have been contrasted not only with a typical uniform mesh algorithm, but also with experimental measurements for a two-wire crosstalk set-up, leading to excellent agreement between theoretical and experimental waveforms. A discussion about the advantages of the non-uniform mesh over the uniform one is also presented.